Edukacja kobiet w XVII i XVIII-wiecznej Anglii i próby przezwyciężenia obowiązującego kanonu - Szczap, Agnieszka (Er(r)go. Teoria - Literatura - Kultura, 2017)
[abstrakt po polsku poniżej] Agnieszka Szczap Institute of Philosophy The University of Zielona Góra Poland Women’s Education in the 17th- and 18th-century England and the Attempts at Surmounting the Canon Abstract: The paper focuses on the opinions of two women thinkers: Mary Astell (1666–1731) and Mary Wollstonecraft (1759–1797), whose modern views have been influential since the second half of the 20th century. The aim of the paper is to foreground the originality in their way of thinking against the background of philosophical views as well as social and cultural situation in the 17th- and 18th-century England. Keywords: feminism, education, Mary Astell, Mary Wollstonecraft, cultural practice of 17th and 18th century England Agnieszka Szczap Instytut Filozofii Uniwersytet Zielonogórski Edukacja kobiet w XVII i XVIII-wiecznej Anglii i próby przezwyciężenia obowiązującego kanonu Abstrakt: W prezentowanym artykule skupiłam się na poglądach dotyczących edukacji kobiet, a szczególnie na poglądach dwóch myślicielek: Mary Astell (1666-1731) i Mary Wollstonecraft (1759-1797), których nowoczesne poglądy były kontynuowane w XX wieku. Ich poglądy polemizowały z dominującymi opiniami na temat sytuacji i roli kobiet w XVII i XVIII-wiecznej Anglii. słowa kluczowe: feminizm, edukacja, Mary Astell, Mary Wollstonecraft, praktyka kulturowa Anglii XVII i XVIII wieku.